Polarization independent and tunable plasmoninduced transparency for slow light - Yang, Hanning; Owiti, Edgar O; Yenpo, Pai; Sun, Xiudong (Royal Society of Chemistry, 2017)
A novel metamaterial composed of a Ag nanoprism periodic tetramer is proposed in this paper. Themetamaterial has high structural symmetry and shows polarization independent plasmon-inducedtransparency (PIT), demonstrated through simulation based on afinite element method. Resonantwavelength and transmissivity of the transparency window isflexibly tuned by changing thefillet radius,the edge length, and the thickness of the Ag nanoprisms. A slow-light effect, caused by an adjustable PITwith a special line shape, can also beflexibly manipulated as the nanoprisms arefilleted. The maximumgroup index value of the metamaterial ranges from 71 to 225. The effects show potential for applicationin novel plasmonic environmental sensors and slow-light devices